Temporal variability of the microbial food web (viruses to ciliates) under the influence of the Black Sea Water inflow (N. Aegean, E. Mediterranean) - GIANNAKOUROU, A.; TSIOLA, A.; KANELLOPOULOU, M.; MAGIOPOULOS, I.; SIOKOU, I.; PITTA, P. (Mediterranean Marine Science, 2014)
Τhe entire pelagic microbial food web was studied during the winter-spring period in the frontal area of the North Aegean Sea. Abundance of viruses, heterotrophic bacteria, cyanobacteria, auto- and hetero-trophic flagellates, and ciliates, as well as bacterial production, were measured at three stations (MD1, MD2, MD3) situated along a N-S transect between the area directly influenced by the inflowing Black Sea water and the area covered by the Levantine water. Samples were collected in December 2009, and January, March, April, and May 2011. Station MD1 exhibited the highest values of abundance and integrated biomass of all microbial groups and bacterial production during all months, and MD3 the lowest. Bacteria dominated the total integrated biomass at all stations and months, followed by cyanobacteria, auto-, hetero-trophic flagellates and ciliates. On a temporal scale, the microbial food web was less important in March as all microbial parameters at all stations showed the lowest values. After the phytoplankton bloom in March, the heterotrophic part of the microbial food web (mainly) strongly increased, though the intensity of the phenomenon was diminished from North to South. Pico-sized plankton was found to be heterotrophic whereas nanoplankton was autotrophic. It seems that the influence of the Black Sea water on station MD1, permanent throughout the study period of early winter to late spring, was reflected in all microbial populations studied, and produced a more productive pelagic food web system, with potential consequences for the upper trophic levels.